Scientific Opinion on Cylactin® (Enterococcus faecium) for calves, lambs and kids for rearing and for fattening - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2013)
Cylactin® consists of dehydrated cells of a strain of Enterococcus faecium. It is authorised for use in feeds for chickens, turkeys and pigs for fattening, piglets, sows, calves and cats and dogs. The applicant is now seeking re-evaluation when used with calves and a new authorisation for use in feed for goat kids and lambs for rearing and for fattening at 1.0 x 109 - 6.6 x 109 CFU/kg feed. The strain does not contain marker genes typical of hospital-associated isolates responsible for clinical infections and is susceptible to clinically relevant antibiotics, except for kanamycin which is considered of no concern. There were no adverse effects seen in calves when Cylactin® was administered at a 100-fold overdose. Consequently, Cylactin® is considered safe for calves for fattening and for rearing at the recommended dose. This conclusion was extended to kids for fattening and rearing. However, lambs for fattening are not considered a minor species and require a separate demonstration of safety which was not provided. No additional concerns would arise for consumers, users and the environment from the proposed extension of use. Seven trials made with calves for fattening or rearing were considered. Use of the additive with calves for fattening significantly increased final body weight and/or daily gain in four of five trials when used at a dose of 1 x 109 CFU/kg complete feed. An additional study with calves for rearing confirmed these results at the same dose. As the mechanism of action of the additive can be reasonably assumed to be same, the positive results seen in calves for fattening and rearing can be extrapolated to kids for rearing and fattening. Conclusions on the efficacy of the product for sheep would derive from results with lambs for fattening which were not made available.